The role of social media in the oral and communicative skills of language learners - Millan-Ramos, Daniel Hernán; Ávalos-Obregón , María Dolores; Quishpe-Hipo , Luis Armando; Cardozo-Cabezas , Kely Estefania (EPISTEME KOINONIA, 2025)
The objective of this research is to explore the influence of social networks on students’ oral skills in English classes. A qualitative field methodology was applied, collecting data to analyze students’ engagement with digital platforms during the first semester of the National and Foreign Languages program at the Universidad Nacional de Chimborazo. The results show that students use social networks as informal learning tools, particularly to improve pronunciation and vocabulary. Many students engage in spontaneous communication in English through digital messages and videos. However, teachers only occasionally incorporate these tools, revealing a disconnect between students’ digital habits and current teaching practices. In conclusion, social networks offer pedagogical opportunities that educators should recognize and leverage to foster meaningful development of oral language skills in English.